Safeguarding Patient Privacy: Exploring Data Protection in E-Health Laws: A Cross-Country Analysis - Patnaik, Sambhabi; Garikapati, Kyvalya; Dash, Lipsa; Bhattacharya, Ramyani; Mohapatra, Arpita (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
INTRODUCTION: Health information amassed during the treatment of a medical condition is termed health data. This data encompasses information gathered about a patient and their family, forming a patient history. The internet has progressively transformed communication, commerce, and information acquisition. Among the diverse domains it has influenced, the healthcare sector stands out as one of the most intricate and unique realms of integration. Big data are the results of normal online transactions and interactions that take place online, the detectors that are implanted in devices and actual locations, as well as the generation of digital contents by individuals whenever they submit data over internet. OBJECTIVES: The need of protection of health data and methods of safeguarding patient privacy. The study also helps and appreciate the best practices which will help India in implementing the law more effectively. METHODS: A doctrinal method of research was employed to analyse the laws and regulations. A comparative approach of different countries gives us the understanding of the gaps and issues. The efficacy of the laws was tested as the paper explores the laws of Canada & Indonesia regarding data protection. RESULTS: In this study, we understood the generation, processing, and interchange of these massive amounts of data can now be facilitated by cloud computing technology. As India, recently enacted ‘The Digital Data Protection Act 2023’ which might be a ray of hope for protection of sensitive health data of individuals from misuse. CONCLUSION: The journey towards optimal data protection is ongoing, requiring continuous adaptation to the dynamic nature of technology and the ever-changing healthcare environment.